Shemer's Estate - Stager, Lawrence E. (Bulletin of ASOR, 1990)
The Joint Expedition to Samaria dated bedrock installations to Early Bronze I and postulated a gap in occupation until the early ninth century B. C., when King Omri established his capital there. It is suggested that the score of olive- and winepresses cut into the bedrock summit were really part of Shemer's (or better, the Shomron family's) estate, which had been in the family since at least Iron I and included not only the center for processing oil and wine, but also the terraced olive- and vineyards that girdled the slopes. Because Samaria I-II pottery spans the 11th and 10th centuries B. C., this site should not be used to lower the Iron Age chronology for other sites in the Levant, Cyprus, or the Aegean.